The effects of high school, community and personal variables on the occupational choices of high school seniors in selected towns in Laguna - Luna, Adelina L. 1933- (s.n.], 1970)
The main purpose of the study is to determine the influence of school, community, and personal variables on the hierarchy of occupational choices of rural high school seniors. Findings of the study reveal that high school seniors in Laguna have a strong preference for professional careers rather than vocational careers although variations in the hierarchy of these preferences are influenced by certain factors. The information derived from the study may provide an understanding for these occupational choices and can be used for restructuring these occupational choices in relation to the needs of national development.